Distribution and sources of heavy metals in the sediment of Xiangshan Bay - Sun, Weiping (2015)
Heavy metals in the surface sediments and sediment core from the Xiangshan Bay, a mariculture base on the coast of the East China Sea, were determined by inductively coupled plasma mass spectrometry (ICP-MS) in order to evaluate their levels and sources. The results showed that the levels of Cu, Pb, Zn, and Cr in the sediments of the bay have been generally influenced by anthropogenic inputs since the founding of the People’s Republic of China. In particular, Cu and Zn were polluted to some extent, as evidenced by high enrichment factors. Organic matter, grain size, wastewater discharge, and low energy hydrodynamic environment played dominant roles in the heavy metal enrichment in the sediments. The ratio of terrigenous source to marine biogenic deposit of trace metals in the sediments was calculated, revealing that terrigenous inputs were the main source of Cu, Pb, and Zn, while biological pellets contributed much more to the enrichment of Cr and Cd. Considering the influence of biological sources on the enrichment of Cd and Cr, and the fact that the sediment has been polluted by Cu and Zn, the development of mariculture and discharge of wastewater into the Bay should be restricted.